Food production, population growth, and environmental security - Gretchen Daily; Partha Dasgupta; Bert Bolin; Pierre Crosson; Jacques du Guerny; Paul Ehrlich; Carl Folke; Ann Marie Jansson; Bengt-Owe Jansson; Nils Kautsky; Ann Kinzig; Simon Levin; et al. (Fondazione Eni Enrico Mattei (FEEM), 1998)
There are two broad criteria by which one can judge humanity's success in feeding itself: (i) the proportion of people whose access to basic nutritional requirements is secure; and (ii) the extent to which global food production is sustainable. Even though the two are related, they have usually been discussed separately in popular writings. This has had unfortunate consequences. Writings on (ii) have often encouraged readers to adopt an all-or-nothing position (viz. the future will be either rosy or catastrophic), and this has drawn attention away from the economic misery that is endemic in large parts of the world today. On the other hand, writings on (i) have frequently yielded no more than the catechism that the nearly 1 billion people in poor countries who go to bed hungry each night do so because they are extremely poor. In short, if (ii) has focused on aggregate food production and its prospects for the future, (i) in contrast has isolated food-distribution failure as a cause of world hunger. In this article we will adopt the view that (i) and (ii) should not be studied separately, that their link can be understood if attention is paid to the dynamic interactions between ecological and economic systems operating primarily at the geographically localised level.
Keywords: 330; Nachhaltige Entwicklung; Bevölkerungsentwicklung; Ernährungssicherung; Welt